Cross Section of the (γ, n)m Reaction for 116Cd Nucleus in the Region of Giant E1-resonance - Mazur, V.M.; Symochko, D.M.; Bigan, Z.M.; Poltorzhytska, T.V.; Derechkey, P.S. (Ukrainian Journal of Physics, 2022)
The isomeric yield ratios and the cross section of the reaction 116Cd(γ, n)115m,gCd have been studied as functions of the energy of gamma quanta. The obtained experimental results have been compared with calculations performed with the use of the TALYS-1.0 software.